Aquaphotomics investigation of the state of water in oral liquid formulation of traditional Chinese medicine and its dynamics during temperature perturbation. (21st September 2022) - Wei, Xiaoying; Zang, Hengchang; Guan, Yongxia; Yang, Cui; Muncan, Jelena; Li, Lian
Abstract : Three types of bound water with different hydrogen bonding strengths were identified and elucidated by aquaphotomics. Abstract : The solvent of the oral liquid formulations of traditional Chinese medicine is mainly water, but the variation of the absorption band of water in the infrared (IR) spectrum was often ignored in previous studies. In this study, the FT-IR spectra of the oral solution for Xiao'er Xiaoji Zhike Oral Liquid (XXZOL) were collected and, using second order derivatives, the OH stretching vibrational band was decomposed into three Gaussian components, whose frequencies were related to the hydrogen bond distance and whose amplitudes were related to the amount of the three types of bound water, differing in structure. Three characteristic peaks at 3400 cm −1, 3200 cm −1 and 3050 cm −1 in the high-wavenumber region of FT-IR spectra of XXZOL were identified, and the dynamic mechanism of the change in its water structure was investigated by two-dimensional (2D) correlation analysis using temperature as a perturbation factor. The specificity of the three characteristic peaks was also validated with pure water and different XXZOL samples. In conclusion, this research has identified three peaks which could be attributed to XXZOL water species and the dynamics of the three peaks were elucidated. It provides a novel idea for the examination of the state of water and solvation dynamic of the oral liquid system of traditional Chinese medicine in the future.